Out on the wire : the storytelling secrets of the new masters of radio - Abel, Jessica (New York : B/D/W/Y/Broadway Books, 2015)
"Go behind the scenes of seven of today's most popular narrative radio shows and podcasts, including This American Life and RadioLab, in graphic narrative. Every week, millions of devoted fans tune in to or download This American Life, The Moth, Radiolab, Planet Money, Snap Judgment, Serial, Invisibilia and other narrative radio shows. Using personal stories to breathe life into complex ideas and issues, these beloved programs help us to understand ourselves and our world a little bit better. Each has a distinct style, but every one delivers stories that are brilliantly told and produced. Out on the Wire offers an unexpected window into this new kind of storytelling--one that literally illustrates the making of a purely auditory medium. With the help of This American Life's Ira Glass, Jessica Abel, a cartoonist and devotee of narrative radio, uncovers just how radio producers construct narrative, spilling some juicy insider details. Jad Abumrad of RadioLab talks about chasing moments of awe with scientists, while Planet Money's Robert Smith lets us in on his slightly goofy strategy for putting interviewees at ease. And Abel reveals how mad--really mad--Ira Glass becomes when he receives edits from his colleagues. Informative and engaging, Out on the Wire demonstrates that narrative radio and podcasts are creating some of the most exciting and innovative storytelling available today"--
"This graphic novel takes readers behind the scenes of their favorite radio shows and podcasts to show the storytelling techniques and ideas that produce these beloved programs"--
Amuse yourself : ideas -- The heat of their breath : character and voice -- Keep or kill : story structure -- The deep sea : sound -- Your baby's ugly : the edit -- Epilogue.
Includes bibliographical references (pages 211-226) and index.
Keywords: Radio -- Production and direction -- Comic books, strips, etc; Podcasts -- Production and direction -- Comic books, strips, etc; Graphic novels -- United States